OTOMASI PERENCANAAN URUTAN PERAKITAN PRODUK DENGAN MEMPERTIMBANGKAN TITIK LOKASI MATING DAN VOLUME KOMPONEN - Alfadhlani
Abstrak: Assembly sequence generation is one among phases in assembly planning. Several researchs have been conducted in the area for automatic assembly sequence generation (Delchambre,1992; Ben-Arieh and Kramer,1994; Onozuka, et al., 1994; Kanai, et al., 1996; Laperriere and ElMaraghy, 1996, Ariastuti, et al., 1998; Tseng and Li, 1999; Toha, et al., 2004). However, common automatic assembly planning methods could not be used directly by a planner. This is so because of intermediate process that has to be done before assembly sequence planning is not obtained. Generally, the necessary input for assembly planning is an engineering drawing of 3D solid. In addition, the feasibility of the sequence should be assured through the process. This research proposes the development of assembly modelling, data extraction algorithm from CAD system, and assembly sequence generation algorithm. Feasibility of the assembly sequence is obtained by considering component and sub-assembly stability in assembly process, geometrical interference, accessibility, and fasteners. Automatic assembly sequence generation is done by using 3D solid input in the form of stacked drawing. Component selection priority rule is based on mating quantity, volume, and mating point location criteria. Application of the model and algorithm on sample products shows that the model can generate a feasible assembly sequence plan for each product.